Analysis The Service Level of Pedestrian Pathways on Jalan Malioboro Yogyakarta - Nursetya, Firman Adjie; Mokhberioskouei, Leila (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
The city's tourism location continues to improve, and the number of visitors is increasing, which is also directly proportional to the number of pedestrians. Malioboro Street has become one of the best pedestrian tourist destinations but has not been accompanied by adequate security and comfort conditions to maintain a good level of pedestrian service. The purpose of this study is to determine the level of service of the pedestrian path, obtain the performance results of the pedestrian path service, and obtain the effective width that meets the needs of the pedestrian path on Malioboro Street Yogyakarta as the input and consideration for the local government in developing facilities and pedestrian support infrastructure. The research uses direct survey observations on the condition of the pedestrian path on Malioboro Street. It collects questionnaires for 100 respondents to see the performance of the pedestrian path on Malioboro Street. The result of this research is the value of the service level of the pedestrian path are varies; the importance of Los is A in the morning and B in the evening for in front of Malioboro Mall then the value of Los is B in the morning and C in the evening for in front of the Afternoon Market. Along with the prediction of creation in pedestrians in the next five years, the Los value from each observation point will drop one level below it.Â Meanwhile, based on research conducted with the IPA method to determine the level of satisfaction of pedestrians on Malioboro Street, the percentage of satisfaction level was 84.16%, which was included in VERY GOOD condition. In addition, the state of the effective width of the pedestrian path on Malioboro Street is by the SE Minister of PUPR 02/SE/M/2018 and can still accommodate pedestrians.